Autophagy, a guardian against neurodegeneration - García-Arencibia, Moisés (Academic Press, 2010)
Autophagy is an intracellular degradation process responsible for the clearance of most long-lived proteins and organelles. Cytoplasmic components are enclosed by double-membrane autophagosomes, which subsequently fuse with lysosomes for degradation. Autophagy dysfunction may contribute to the pathology of various neurodegenerative disorders, which manifest abnormal protein accumulation. As autophagy induction enhances the clearance of aggregate-prone intracytoplasmic proteins that cause neurodegeneration (like mutant huntingtin, tau and ataxin 3) and confers cytoprotective roles in cell and animal models, upregulating autophagy may be a tractable therapeutic strategy for diseases caused by such proteins. Here, we will review the molecular machinery of autophagy and its role in neurodegenerative diseases. Drugs and associated signalling pathways that may be targeted for pharmacological induction of autophagy will also be discussed.